Isolated potato parenchyma cells: Physico-chemical characteristics and gastro-small intestinal digestion in vitro. (November 2020) - Do, Duc Toan; Singh, Jaspreet; Oey, Indrawati; Singh, Harjinder
Abstract: Intact parenchyma cells and native starch granules were isolated from Agria and Sunlite potato ( Solanum tuberosum L.) cultivars. Their morphology, physicochemical properties, and in vitro starch digestion were investigated. Parenchyma cells varied in shape, size, and composition. Each cell contained numerous starch granules enveloped by a cell wall. Starch inside Agria cells exhibited higher gelatinisation temperatures than isolated Agria starch. For both cultivars, starch inside cells had higher peak and breakdown paste viscosities than isolated starch. Cooked cells and isolated starches exhibited similar in vitro starch hydrolysis profiles. These results indicate that the entrapment of starch granules in parenchyma cell walls affected thermal and pasting properties of starch, but had no effect on starch digestion kinetics in vitro . The study provides evidence supporting the use of dehydrated parenchyma cells by the food industry for development of novel potato-based food products with desirable physical properties. Graphical abstract: Image 1 Highlights: Starch granules are trapped in parenchyma cell walls of potatoes. Cell walls could restrict granule swelling and delay starch gelatinisation. Cell walls remained reasonably intact during cooking and enzymatic digestion. Alpha-amylase diffused through cell walls to access starch substrate.